2021
DOI: 10.21203/rs.3.rs-143454/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impacts of Chinese drug volume-based procurement policy on the volume and expenditure of antibiotic drugs

Abstract: Background: In 2019, Chinese government implemented the first round of National Centralized Drug Procurement (NCDP) pilot (so-called "4+7" policy) in mainland China, in which an oral antibiotic agent (cefuroxime axetil) was included. Given the current condition of the irrational use of antibiotics in China, this study aims to evaluate the potential effect of the "4+7" policy on antibiotic use. Methods: This study used drug purchasing order data from the Centralized Drug Procurement Survey in Shenzhen 2019, cov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We supposed there is certain possibility that the price of drugs without policy intervention have increased after policy implementation. The increasing of DDDc for the non-winning and the alternative drugs might be related to the unreasonable prescription behavior, such as increased daily doses of some antihypertensive drugs [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…We supposed there is certain possibility that the price of drugs without policy intervention have increased after policy implementation. The increasing of DDDc for the non-winning and the alternative drugs might be related to the unreasonable prescription behavior, such as increased daily doses of some antihypertensive drugs [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of NCDP policy has achieved remarkable results in improving the accessibility of policy-related drugs [14][15][16], promoting the substitution use of generic drugs [17], and increasing overall drug use quality level of the public [18]. However, several previous studies reported an upward trend in the consumption of policy-related drugs after the implementation of NCDP policy [11,19], which should be concerned, especially for the incrased consumption of drugs have not been covered by NCDP policy. For drugs did not covered by volume-based procurement, the increase in usage might be explained that the gray interest chain between physicians and pharmaceutical enterprises still exists, and physicians still have the motivation to prescribe more medicines or choose higher-priced medicines [20].…”
Section: Introductionmentioning
confidence: 99%